Effect of Calcitriol on Bone Turnover and Osteocalcin in Recent-Onset Type 1 Diabetes - Napoli, Nicola (Public Library of Science, 2013)
BACKGROUND: Vitamin D supplementation in childhood improves the achievement of peak bone mass. We investigated the effect of supplementation with calcitriol on bone turnover in recent-onset type 1 diabetes (T1D). Moreover, the association between osteocalcin and parameters of β-cell function and metabolic control was examined. METHODOLOGY/PRINCIPAL FINDINGS: We conducted a post-hoc analysis of a double-blind, placebo-controlled study of calcitriol supplementation to preserve β-cell function. 27 recent-onset T1D subjects, mean age 22 years, were randomized to 0.25 µg calcitriol per day or placebo (1∶1) and followed up for one year. Changes in bone formation (osteoclacin) and resorption (beta-CrossLaps) markers, and differences between placebo and calcitriol-treated group were evaluated. At baseline, osteocalcin levels were significantly lower in female than in male patients (P<0.01) while no other metabolic parameters as HbA1c and C-peptide differed between gender. No significant correlations were found in relation to HbA1c, insulin requirement and C-peptide. At 1 year follow-up, no significant differences were observed between calcitriol and placebo groups for osteocalcin and β-CrossLaps. In the placebo group osteocalcin levels were unrelated with parameters of metabolic control, such as C-peptide, insulin requirement or HbA1c. Changes of C-peptide, insulin requirement and HbA1c were not related to osteocalcin levels. CONCLUSIONS: Supplementation with 0.25 µg calcitriol per day to patients with new-onset T1D does not affect circulating markers of bone turnover. OC levels were unrelated to β-cell function and other metabolic parameters suggesting that OC is ineffective to control pancreatic function in presence of aggressive autoimmune destruction.